(3GdVeGfGJ GdbGfhfjI ddESJKeGQGJ GdCLfHjI ai Ohd eLdS GdJYGhf dOhd GdNdjL GdYQHjI WHbkG ddJTQjYGJ GdhWfjI hGdEJaGbjGJ GdOhdjI (B: s (3OQGSI ebGQfI eY GdbGfhf GdeUQj (B/ s - (3JgGfj YfjRGf UGdM GdQTjOjs; (3SejMI GdbdjhHj s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2015)
(3JJSGHb GdOhd dLPH GdGSJKeGQGJ GdCLfHjI GdJi JQi ajgG YdGLkG fGLYkG deTcdGJgG GdGbJUGOjI(B: (3hdSO YLR eONQGJgG GdbhejI(B: (3hJMSjf ehGRjf eOahYGJgG(B: (3hai SHjd Pdc JJNP Jdc GdOhd ef GdhSGFd eG jcad RjGOI eG jJOab EdjgG ef QCS GdeGd GdCLfHi HCf JRjd GdYbHGJ GdJi JYJQV WQjbg(B: (3hCf JjSQ dg GdELQGAGJ (B: (3hCf JbOe dg GdMhGaR hGdeRGjG GdJi dG JJYGQV hGbJUGOjGJgG Ef JTQjYGJ GdGSJKeGQ ai Ohd eLdS GdJYGhf GdNdjLi heUQ(B:(3hcPdc GdGJaGbjGJ GdOhdjI GdJi CHQeJgG JLeY Ydi hVY GdbhGYO GdJi Jcad GdVeGfGJ GdbGfhfjI GddGReI ddGSJKeGQ GdCLfHi hGdJi ef CgegG(B: (3JgjFI efGN GdGSJKeGQ(B: (3hGdKHGJ GdJTQjYi(B: (3hGdVeGfGJ VO GdELQGAGJ GdeGSI HGdedcjI cGdeUGOQI hGdJCeje hfRY GdedcjI hMQjI GdJUQa ai GdGSJKeGQ hJMhjd GdCehGd(B. s
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdJLGQi, (B2015s
(3HHdjhLQGajG(B: (3UaMGJ (B435-461s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdJLGQjs; (3GdGSJKeGQ GdGLfHjs; (3YbO GdGSJKeGQ GdGLfHj s; (3GdGSJKeGQ GdMbjbj h GdeGdjs; (3JLGQjI YbO GdGSJKeGQs; (3GdefGN GdGSJKeGQjs; (3GdKHGJ GdJTQjYjs; (3MXQ fRY GdedcjI ddGSJKeGQGJ GdGLfHjIs; (3GdJMcje aj efGRYGJ GdGSJKeGQs; (3bGfhf GdGQGOIs; (3GJaGbjGJ GdGSJKeGQ aj eLdS GdJYGhf GdNdjLjs; (3GdGJaGbjI GdehMOI dGSJKeGQ QDhS GdGehGd GdYQHjI ai GdOhd GdYQHjI dYGe (B1980s; (3GJaGbjI GdeQcR GdOhdj dJShjI efGRYGJ GdGSJKeGQ hGTfWf (B1965s; (3GJaGbjI JfXje GLQGAGJ GdGSJKeGQ GdeQJHWI HJLGQI GdSdY dYGe (B1994s; (3GJaGbjI GdhcGdI GdOhdjI dVeGf GdGSJKeGQs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdJLGQjs